Response of phase I and II detoxification enzymes, glutathione, metallothionein and acetylcholine esterase to mercury and dimethoate in signal crayfish (Pacifastacus leniusculus). (October 2018) - Gunderson, Mark P.; Nguyen, Brandon T.; Cervantes Reyes, Juan C.; Holden, Laura L.; French, John M.T.; Smith, Brandon D.; Lineberger, Connor
Abstract: Metals and pesticides are common pollutants and the modulation of biomarkers can indicate sub-lethal influences on the physiology of organisms inhabiting impacted aquatic systems. We examined the effects of mercury and the organophosphate pesticide dimethoate on EROD, MROD, glutathione S-transferase (GST), acetylcholine esterase (AChE), metallothionein (MT) and glutathione (GSH) in the signal crayfish ( Pacifastacus leniusculus ). Crayfish were injected with mercury chloride or dimethoate (0.3, 0.6, 0.9 μg kg −1 ) and dissected after 72 h. EROD activity in the hepatopancreas did not change in response to mercury chloride treatment but exhibited a dose dependent decrease at all concentrations of dimethoate tested. MROD (hepatopancreas) exhibited a significant decrease at the 0.9 μg kg −1 treatment for both chemicals. GST (hepatopancreas) demonstrated a significant dose dependent decrease at all concentrations of both mercury chloride and dimethoate. AChE (tail muscle) decreased at the 0.6 and 0.9 μg kg −1 concentrations of dimethoate and 0.9 μg kg −1 mercury chloride. In gill tissue, MT increased in response to 0.3 and 0.6 μg kg −1 of mercury chloride but no effect was observed at the 0.9 μg kg −1 concentration of mercury chloride or any concentrations of dimethoate tested. MT did not change in response to mercury or dimethoate in tail tissue. Furthermore, neither chemical modulated GSH concentrations. Our results indicate that, apart from GSH, these markers are sensitive to the pollutants tested and that animals exposed in the wild are potentially compromised in their ability to detoxify environmental contaminants and carry out normal cellular processes. Highlights: EROD, MROD, GST and AChE are sensitive to dimethoate exposure in signal crayfish. MROD, GST, MT and AChE are modulated by mercury chloride. Decreased phase I and II enzymes could impact overall biotransformation capability. AChE inhibition could cause increased mortality or altered physiological function.